EFFECT OF TOURIST CHARACTERISTICS AND RESOURCES ON IMAGE: STUDY OF CILETUH GEODIVERSITY AREA SUKABUMI - Ernie Tisnawati Sule (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2020)
Ciletuh Geopark, located in Sukabumi regency, is one of the promising tourist destinations in West Java. This research aims to explore the effect of tourist characteristics and resources on the image of Ciletuh Geopark. This research is quantitative, employing a time horizon of cross-sectional. The analysis unit of this research is visitors at the geodiversity area of Ciletuh, while the observation unit is the visitors or tourists visiting this area at the end of 2019. The sample of this study is 100 visitors. The partial least square (PLS) is used for analyzing the causal relationship between variables. The research results show that tourist characteristics and resources affect the image. Resources have a more substantial effect than the tourist characteristics do. This study implies that the management of Ciletuh Geopark needs to pay more attention to developing and managing the resources, primarily the natural resources, cultural resources, and human resources. Besides, this effort needs to be supported by the understanding of tourist characteristics. Hence, the image of the destination will be enhanced.